High Rate of Unemployment and Yoof Disillusionment in Taraba State, Nigeria: Entrepreneurship Education as Antidote - Andeyangtso Bulus; Besonggem Ako; Duguba Agwaru Ezekiel; Musa Dansozon; Bello Ibrahim Muhammed (Genius Publishing Group, 2022)
This paper examines the high rate of unemployment and youth disillusionment in Taraba State, Nigeria, and proposes entrepreneurship education as a solution to this problem. Entrepreneurial skills are those skills that an entrepreneur needs to successfully add value to their work. Every Nigerian aspires to be self-sufficient, but only a small proportion of those who try succeed. Too many people give up on their dreams far too soon, when education and mentoring could lead to success. The scarcity of entrepreneurs or people with entrepreneurial mindsets has been one of the major impediments to the development of a vibrant indigenous private sector in Nigeria